Anaerobic digestion of nine varieties of grape pomace: Correlation between biochemical composition and methane production. (December 2017) - El Achkar, Jean H.; Lendormi, Thomas; Hobaika, Zeina; Salameh, Dominique; Louka, Nicolas; Maroun, Richard G.; Lanoisellé, Jean-Louis
Abstract: In the present study, nine different varieties of deseeded grape pomace were analyzed for the biochemical composition of the raw material (total solids, volatile matter, total chemical oxygen demand, cellulose, hemicellulose, lignin, total soluble compounds and polyphenols). The biological methane potential of the substrates was assessed in batch anaerobic digesters. The results showed that the cumulative methane yields varied widely and ranged from 102 to 300 dm 3  kg −1 of total solids, calculated at standard gas conditions of 273 K and 101.5 kPa. The anaerobic biodegradability of the total chemical oxygen demand varied between about 30% to a maximum of 69%. The data obtained were exploited by principal component analysis. The study revealed that lignin and cellulose, explaining almost 63% of the total variance in the data, are the main factors limiting the degradability of the selected grape pomace. The effects of the other parameters, which represent nearly 32% of the total variance, were fully reviewed. In particular, no significant correlation was found between the polyphenol content and the methane yield. Graphical abstract: Highlights: Methane production can be a sustainable option for the recovery of the grape pomace. Methane potential was positively correlated with hemicellulose and soluble components fractions. Lignin and cellulose were the main factors limiting the anaerobic biodegradability of grape pomace. Grape pomace pretreatment prior to anaerobic digestion process is required to improve the methane potential. No significant correlation was observed between polyphenol content and methane production.